2013
DOI: 10.4104/pcrj.2013.00062
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to, and facilitators for, referral to pulmonary rehabilitation in COPD patients from the perspective of Australian general practitioners: a qualitative study

Abstract: Background: Pulmonary rehabilitation (PR) is recommended in the management of people with chronic obstructive pulmonary disease (COPD), but referral to this service is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(135 citation statements)
references
References 37 publications
6
120
0
9
Order By: Relevance
“…Supporting this, a larger study from Australia [12] found that 10 of 12 general practitioners interviewed had not directly referred a person with COPD for pulmonary rehabilitation, and barriers among the general practitioners were low knowledge of rehabilitation management of people with COPD.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Supporting this, a larger study from Australia [12] found that 10 of 12 general practitioners interviewed had not directly referred a person with COPD for pulmonary rehabilitation, and barriers among the general practitioners were low knowledge of rehabilitation management of people with COPD.…”
Section: Discussionmentioning
confidence: 96%
“…When benefits are so evident and among other things increases functional capacity and individual control, they can lead to a more active daily life with less admission to hospital for exercabation of symptoms [12] and probably less pathological changes in the lungs – and possibly prevent disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of frequent exacerbations (16% of patients) and an average of 1.24 hospitalizations per year because of COPD exacerbations suggest that the awareness for these as the main drivers of morbidity and cost has to be increased and that rehabilitation and self-management education need to be proclaimed as effective preventive actions, in analogy to programs established for heart disease (32). A recently published report by Australian GPs identified an awareness barrier, insufficient knowledge of how to refer for pulmonary rehabilitation, anticipated access difficulties for patients and cost benefit issues as major problems (33).…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
“…KOAH alevlenme nedeniyle hastanede yatış sırasında veya hemen akabinde uygulanan PR programlarının çok yararlı ve maliyet etkin olduğu gösterilmiştir [20,23,24]. Ancak, KOAH alevlenme nedeniyle hastanede yatış sonrası PR'a sevk edilme ve uygulama oranları tüm dünyada hala çok düşük seyretmektedir [25][26][27]. Bizim ülkemiz için bildirilen bir oran olmamakla birlikte PR konusunda hizmet veren merkezlerin sayısının oldukça sınırlı olması ve bu konudaki bilgi eksikliği nedeni ile beklenen oran oldukça düşüktür.…”
Section: Bulgularunclassified